Simulation of antisolvent crystallization in impinging jets with coupled multiphase flow-micromixing-PBE. (2nd November 2017) - Cheng, Jingcai; Yang, Chao; Jiang, Mo; Li, Qian; Mao, Zai-Sha
Highlights: High-resolution central schemes by Kurganov & Tadmor is extended to general form. The coupled multiphase flow-micromixing-PBE model is developed. The model is validated in OpenFOAM for antisolvent crystallization of lovastatin. The effect of the existence of crystal phase on flow field and CSD is studied. Geometric size partition considerably improves predicted CSDs in some cases. Abstract: The KT (Kurganov and Tadmor, 2000) finite-volume central scheme is one of the most promising high-resolution numerical methods to solve the widely-used population balance equation (PBE) in crystallization and other areas. To meet the practical purpose of geometric-type particle size grid, the primary KT scheme was extended to a general form and validated for pure growth in homogeneous systems. Based on the extended KT scheme, a solver was developed that couples the general discretized PBE and amicromixing and a CFD mixture model in OpenFOAM (open-source field operation and manipulation). The simulation uses published parameters from and is compared to experimental antisolvent crystallization of lovastatin from a methanol-water mixture in an impinging jet. The effect of the existing solid crystals on some crystal properties is investigated in this work for the first time. The shapes of crystal size distribution (CSD) at various jet velocities are consistent with experimental observations. The geometric particle size partition is shown to be capable of improving the accuracy of simulation in divisions of the highest particle number densities or steep gradients in the number density. The existing solid crystals are also shown to have a non-negligible effect on the slurry flow crystallization systems once the mean crystal size reaches 20 µm.